Mikrobiota usus pada dermatitis atopik - Dewi Gotama; Made Wardhana; Adeline Santoso; Sissy Sissy (DiscoverSys Inc., 2021)
Atopic dermatitis (AD) is a multifactorial disease caused by immune dysregulation, genetic susceptibility, environmental factors, and impaired barrier function. The health burden caused by this disease is significant and can impact psychological, social and financial costs, along with systemic comorbidities. Several studies have reported the gut microbiota in AD patients. Several studies have reported the gut microbiota in AD patients. The gut microbiota is thought to play an important role in the development of AD by regulating the immune system's maturation. Intestinal microbiota alteration affects the balance of the immune system through metabolites' production, which will cause the microenvironment to become inflamed. Currently, the close relationship between the gut microbiota and the development of the immune system, especially in maintaining the balance of Th-1 and Th-2 responses, is the rationale for providing probiotic supplements to prevent or treat allergic and atopic diseases. Dermatitis atopik (DA) merupakan penyakit multifaktorial yang diakibatkan disregulasi imun, suseptibilitas genetik, faktor lingkungan, dan gangguan fungsi barier. Beban kesehatan yang diakibatkan penyakit ini bersifat signifikan dan dapat berdampak pada kerugian psikologis, sosial, dan finansial, disertai komorbiditas sistemik. Terdapat beberapa studi yang telah melaporkan mikrobiota usus pada pasien DA. Mikrobiota usus diduga memainkan peran penting dalam perkembangan DA dengan meregulasi maturasi sistem imun. Alterasi mikrobiota usus mempengaruhi keseimbangan sistem imun melalui produksi metabolit, yang akan menyebabkan lingkungan mikro mengalami inflamasi. Saat ini hubungan erat antara mikrobiota usus dan perkembangan sistem imun, khususnya dalam menjaga keseimbangan respon Th-1 dan Th-2 menjadi dasar pemikiran pemberian suplemen probiotik untuk mencegah atau mengatasi penyakit alergi dan atopi.